Penerapan 5S untuk Pengelolaan Gudang Sparepart Pesawat dalam Sistem Logistik Industri MRO - Mardhiyyah Cahaya Chalia; Wiku Larutama (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The spare parts warehouse plays an important role in supporting the smooth operation of aircraft Maintenance, Repair, and Overhaul (MRO) activities. This study aims to analyze the spare parts warehouse management at PT XYZ and evaluate the implementation of the 5S method to improve operational efficiency. A qualitative approach was employed through participant observation and documentation during an internship program. The results indicate that, prior to the implementation of 5S, the warehouse faced several issues, including a non-integrated recording system, unstructured storage layout, and the presence of unidentified spare parts (anonymous parts). These conditions resulted in longer spare part retrieval times, increased waste, and potential delays in aircraft maintenance processes. The implementation of the 5S method improved warehouse organization, spare part identification, and material accessibility and control, thereby enhancing operational efficiency. Continuous monitoring and evaluation are required to sustain and further improve the achieved results.